The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1242/jcs.115.16.3285
|View full text |Cite
|
Sign up to set email alerts
|

Staufen2 isoforms localize to the somatodendritic domain of neurons and interact with different organelles

Abstract: Mammalian Staufen2 (Stau2) is involved in mRNA transport in neurons. Here,we report that Stau2 is a double-stranded RNA-binding protein that is mainly expressed in the brain. We show that Stau2 is found in the somatodendritic compartment of neurons. In dendrites, Stau2 is aligned on individual tracts and colocalizes with microtubules. Stau2 is expressed as at least three splice isoforms, which can be observed in several subcellular complexes. Although a 62 kDa isoform (Stau262) fractionates in ribosome-free fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(17 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…STAU1 and STAU2 are a dsRBP. They are found in stress granules (SGs) in brain oligodendrocytes and neurons and modulate SG dynamics 13,[41][42][43] . Owing to Staufen's ability to function as an RBP, it is involved in regulating RNA metabolism, mRNA transport in neuronal dendrites, and other cells in vertebrates [44][45][46] .…”
Section: Discussionmentioning
confidence: 99%
“…STAU1 and STAU2 are a dsRBP. They are found in stress granules (SGs) in brain oligodendrocytes and neurons and modulate SG dynamics 13,[41][42][43] . Owing to Staufen's ability to function as an RBP, it is involved in regulating RNA metabolism, mRNA transport in neuronal dendrites, and other cells in vertebrates [44][45][46] .…”
Section: Discussionmentioning
confidence: 99%
“…Besides being an RNA granule-forming protein by means of RNA-protein and protein-protein interactions (21,31,32) Staufen associates to and regulates the translational apparatus (33)(34)(35). We and others have demonstrated that Staufen 1 and 2 associates to polysomes located at myelin processes and at post-synaptic densities (33,34), and to polysomes and ribosomal subunits in primary neurons and fibroblast cells lines, all this supporting a regulatory role in translation (11,16,31,35). More recently, we have found that Staufen is a conserved component of SGs, which are granular accretions of RNPs specifically assembled in a transient manner during the cellular response to stress.…”
Section: Introductionmentioning
confidence: 69%
“…In recent years, a number of research groups have focused on this highly conserved protein and its role on the regulation of cytoplasmic post-transcriptional processes in mammalian CNS cells (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Two paralog genes are present in vertebrates, Staufen 1 and Staufen 2, and both proteins have been implicated in mRNA localization.…”
Section: Introductionmentioning
confidence: 99%
“…This study reveals that STAU1 can take three different conformations in solution, that it is a highly flexible protein and highlights the importance of neighbouring double‐stranded RNA‐binding domains (dsRBDs) for substrate specificity. STAU1 binds RNA through two dsRBDs (dsRBD3 and 4) which both adopt a canonical α–β–β–β–α dsRBD fold (Wickham et al ., 1999; Ramos et al ., 2000; Duchaine et al ., 2002; Martel et al ., 2010; Gleghorn et al ., 2013; Gleghorn & Maquat, 2014; Lazzaretti et al ., 2018; Visentin et al ., 2020; Yadav et al ., 2020). It is proposed that the flexible dsRBD3/4 tandem recognizes RNA in a multistep process: dsRBD3 recognizes and scans dsRNAs, allowing the recruitment of dsRBD4 on the SBS.…”
Section: Stau1 Regulates Diverse Classes Of Rnas Involved In Various ...mentioning
confidence: 99%
“…Two Staufen paralog genes, STAU1 and STAU2 , are expressed from different loci in vertebrates (Buchner et al ., 1999; Brizard, Luo & DesGroseillers, 2000). Although STAU1 and STAU2 proteins are sometimes found as heterodimeric complexes (Park, Gleghorn & Maquat, 2013), they mostly form independent ribonucleoprotein complexes (RNPs) and regulate different physiological pathways (Duchaine et al ., 2002; Furic, Maher‐Laporte & DesGroseillers, 2008; Lebeau et al ., 2008, 2011; Hassine et al ., 2020). In this review, we focus on STAU1 and review recent evidence linking STAU1 to post‐transcriptional regulation of gene expression and to cancer.…”
Section: Introductionmentioning
confidence: 99%